METHODOLOGICAL BASES OF THE SYSTEM OF INTERNAL CONTROL OF ENTERPRISES IN MODERN MARKET CONDITIONS - Yu. S. Sulenova (Publishing House of the State University of Management, 2020)
At the present stage, in the course of conducting financial and economic activities serious importance is attached to effective methodology for assessing internal control system. Using necessary methodological tools, foreign standards of internal control and the mechanism for forming the internal control system in Russian organizations, taking into account both foreign and Russian experience, have been studied in this article. A comparative analysis of the concepts of COBIT and COSO also has been presented, the models of COBIT and COSO in the context of all components of these models have been analyzed, key indicators for developing a methodology for evaluating the internal control system, aimed at improving the competitiveness of an economic entity in modern market conditions, have been defined.